Longitudinal and Temporal Evolution of the Tectonic Style Along the Cyprus Arc System, Assessed Through 2‐D Reflection Seismic Interpretation. Issue 1 (3rd January 2018) - Symeou, Vasilis; Homberg, Catherine; Nader, Fadi H.; Darnault, Romain; Lecomte, Jean‐Claude; Papadimitriou, Nikolaos
Abstract: The Cyprus Arc system constitutes a major active plate boundary in the eastern Mediterranean region. This structure is directly linked with the northward convergence of the African and Eurasian plates since the Late Cretaceous. Two‐dimensional reflection seismic data were utilized, which image the main plate structures and their lateral evolution south of the island of Cyprus. Interpretation of these data allowed the identification of nine tectono‐sedimentary packages in three different crustal domains south of the Cyprus Arc system: (1) the Levant Basin (attenuated continental crust), (2) the Eratosthenes microcontinent (continental crust), and (3) the Herodotus Basin (oceanic crust). Within these domains, numerous tectonic structures were documented and analyzed in order to understand the mechanism and timing of deformation. In the north, south verging thrusting commenced in early Miocene along the Larnaca and Margat ridges, whereas no activity was identified before middle Miocene along the Latakia Ridge. Thus, the deformation front migrated southward and was accompanied by the development of flexural basins and stratigraphic onlaps as in the Cyprus Basin. The acme of deformation occurred in mid‐late Miocene. A regional unconformity of Pliocene age marks the end of the first deformation sequence. In Plio‐Pleistocene time, the westward escape of the Anatolian microplate resulted in the reactivation of existing structures. The evolution of deformation along the plate boundary is identified from the creation of positive flower structures revealing transpressive movements along the Larnaca and Latakia Ridges (eastern domains), whereas in the Eratosthenes domain a flexural basin highlights a compressive regime. Plain Language Summary: The Cyprus Arc system is situated at the boundary of the Arabian, African, and Eurasian plates and is associated with a convergent setting, which is active since the Late Cretaceous, in response to the northward movement of the African plate with respect to the Eurasian plate. Two‐dimensional seismic interpretation resulted in the identification of different crustal domains, which are the following: (1) the Levant Basin, (2) the Cyprus Basin, (3) the Eratosthenes Seamount, and (4) the Herodotus basin. These domains are underlain by a different crustal nature and record contractional pulses from Neogene to Recent time. Thrusting activity is dominant in Miocene time on the Latakia, Margat, and Larnaca Ridges, with the deformation style best described by a forward propagation model. In Plio‐Pleistocene time a strike‐slip component is observed, which is associated with the westward escape of the Anatolian microplate. In this contribution the longitudinal evolution along the Cyprus Arc is presented in relation with the differential crustal nature of each domain. Key Points: Lateral changes from a compressional to a strike‐slip regime along the Cyprus Arc Different crustal nature in the eastern Mediterranean Forward propagation of thrusting toward the south